Does poverty increase COVID-19 in Africa? A cross-country analysis - Etayibtalnam Koudjom; Sévérin Tamwo; Koffi Délali Kpognon (Health Economics Review, 2022)
Background: Most economies in African countries are informal. As such, households in these countries tend to face higher levels of informality coupled with a lack of social protection, and have no replacement income or savings in the event of unexpected external shocks, such as COVID-19. Thus, the COVID-19 shock and its negative economic efects triggered a cascade of income losses and bankruptcies that pushed a signifcant share of households in African countries into poverty. This research analyzes the efect of poverty on the spread of COVID-19 using a sample of 52 African countries. Methods: To achieve the objective of this research, this paper uses a multiple linear regression model and a sample of 52 African countries observed in 2020 to conduct a cross-country analysis. More importantly, two COVID-19 indicators (total number of ofcially reported cases and disease severity) and six poverty indicators (average poverty, poverty incidence, poverty depth, poverty severity, multidimensional poverty index, and extreme poverty) were used in this research. Results: The results show a positive and signifcant relationship between poverty and the spread of COVID-19. Conclusions: These results suggest that more attention needs to be paid to poor populations in African countries during the pandemic. These populations are generally vulnerable, and there is a need for support programs targeting them to be put in place quickly. These programs may include food aid, distribution of supplies, health care support, fee waivers, and interest deferrals. In addition, sensitization of these disadvantaged groups on vaccination against COVID-19 to achieve herd immunity is strongly encouraged.
Keywords: I10; I32; 330; COVID-19; Poverty; Africa